2006
DOI: 10.1007/s00253-005-0283-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for improving the productivity of ubiquinone-10 producing strain by low-energy ion beam irradiation

Abstract: Agrobacterium tumefaciens ATCC4452 cells were irradiated by nitrogen ion beam, a new mutagen, with energy of 10 keV and fluence ranging from 2.6x10(14) ions/cm2 to 6.5x10(15) ions/cm2. A similar "saddle shape" survival curve due to ion beam irradiation appeared again in this study. Some mutants with high yield of ubiquinone-10 were induced by ion implantation. High mutation rate and wide mutation spectrum were also observed in the experiment. These results suggested that the mutagenic effect of such low-energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…This is due to the controllable damage rate, higher mutation rate, and wider spectrum of mutations obtained by N + ion beam implantation compared to traditional mutation methods (Feng et al 2006). In recent years, many achievements have been realized by using N + ion beam implantation (Ge et al 2004;Gu et al 2006;Gong et al 2009;Wang et al 2011). However, there are as yet few reports on improving the vitamin K 2 production of B. subtilis (natto) by N + ion beam implantation.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the controllable damage rate, higher mutation rate, and wider spectrum of mutations obtained by N + ion beam implantation compared to traditional mutation methods (Feng et al 2006). In recent years, many achievements have been realized by using N + ion beam implantation (Ge et al 2004;Gu et al 2006;Gong et al 2009;Wang et al 2011). However, there are as yet few reports on improving the vitamin K 2 production of B. subtilis (natto) by N + ion beam implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Through 26 years of development, the technique has made much progress and has been widely applied in the breeding of crops, plants and microbes [7]. Ion implanted is characterized by a higher mutation rate and wider mutational spectrum with less damage for the implanted organism, and suggested that a combination of energy deposition, mass deposition and charge exchange of energetic ions will result in genetic damage [8].…”
Section: Introductionmentioning
confidence: 99%
“…Low-energy ion beams interrupt intracellular contents through cell wall or cell membrane modifications and cause a series of internal or external reactions. Various studies have implemented ion implantation and bombardment, and this technique is typically applied in breeding studies, including rice, wheat, flowers, and microbes (Wu et al, 1990;Morishita et al, 2003;Okamura et al, 2003;Yamaguchi et al, 2003;Gu et al, 2006;Liang et al, 2008). Most of these previous studies only observed variations in the external shape of organisms for improving biomass yield.…”
Section: Discussionmentioning
confidence: 99%